Peringkasan Dokumen Berdasarkan Metode Semantic Sebaran Kalimat - Wahib, Aminul; Sari, Dita Lupita (Universitas Atma Jaya Yogyakarta, 2017)
Abstract. Sentence distribution method performs weighting based on the sentence distribution without taking the semantic meaning of the sentence spread into account. In fact, the semantic relation between sentences is believed to increase the relevance of the search results document. This study proposes new strategies to summarize documents using the semantic sentence distribution method in an effort to improve the quality of the summary. The experimental results show that the proposed method has better performance with the average performance ROUGE-1 0.412, an increase of 1,9% compared to